2015
DOI: 10.1039/c5an00840a
|View full text |Cite
|
Sign up to set email alerts
|

Investigating carbohydrate isomers by IMS-CID-IMS-MS: precursor and fragment ion cross-sections

Abstract: Ion mobility spectrometry techniques (IMS and IMS-IMS) combined with collision-induced dissociation (CID) and mass spectrometry (MS) are used to investigate the structures of singly-lithiated carbohydrate isomers. With the exception of some favorable cases, IMS-MS analyses of underivatized carbohydrates reveal that most isobaric precursor ions have similar collision cross sections (ccs). In contrast, ccs values for isomeric fragment ions obtained by IMS-CID-IMS-MS analysis are often different, and thus appear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 41 publications
1
67
0
Order By: Relevance
“…2. Their drift-time distributions overlap, making them virtually indistinguishable by ion mobility, as reported previously for glycans of this size [13]. We then measured their vibrational spectra, using hydrogen as the tag molecule and keeping the trap temperature at 13 K. As one can see in Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…2. Their drift-time distributions overlap, making them virtually indistinguishable by ion mobility, as reported previously for glycans of this size [13]. We then measured their vibrational spectra, using hydrogen as the tag molecule and keeping the trap temperature at 13 K. As one can see in Fig.…”
Section: Resultsmentioning
confidence: 76%
“…The mobility of an ion through a gas is related to its orientationally averaged collisional cross section (CCS), which reflects its overall shape. While in some cases the structures of different isomeric glycan species can be distinguished by their CCS, in many others cases the structural differences are too subtle to detect in this way [13]. To solve this fundamental problem, one needs to add an orthogonal dimension to these measurements that will allow the discrimination between any pair of isomeric glycans.…”
Section: Introductionmentioning
confidence: 99%
“…Ion mobility spectrometry is a powerful tool for the gas-phase separation of carbohydrates, either as a standalone technique 115,116 or via coupling with other analytical techniques 117 . A recent study has shown that non-derivatized glycans can be separated through a reversed-phase column on a liquid chromatography-ion mobility-mass spectrometry (LC-IM-MS) instrument 118 .…”
Section: Ease Of Coupling To Other Techniquesmentioning
confidence: 99%
“…Although its hyphenation with MS in commercial instrumentation is a more recent development, it has already created new possibilities for the characterization of some classes of small molecules and metabolites [9][10][11]. Specific examples are the separation of isomeric disaccharides [12][13][14] and metal(-ligand) complexes [15][16][17] or the characterization of carbohydrate, glycan and lipid structures [18][19][20][21][22][23]. Particular interest recently focused on the phenomenon of alternative charge sites in small molecules that are observed in the gas phase, i.e.…”
Section: Introductionmentioning
confidence: 99%